2015
DOI: 10.1021/acs.est.5b04310
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Inactivation of Escherichia coli and MS2 Coliphage by Cupric Ion in the Presence of Hydroxylamine: Dual Microbicidal Effects

Abstract: The inactivation of Escherichia coli and MS2 coliphage by Cu(II) is found to be significantly enhanced in the presence of hydroxylamine (HA). The addition of a small amount of HA (i.e., 5-20 μM) increased the inactivation efficacies of E. coli and MS2 coliphage by 5- to 100-fold, depending on the conditions. Dual effects were anticipated to enhance the biocidal activity of Cu(II) by the addition of HA, viz. (i) the accelerated reduction of Cu(II) into Cu(I) (a stronger biocide) and (ii) the production of react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 31 publications
0
37
0
Order By: Relevance
“…It has been previously reported that NH 2 OH was able to efficiently transform Cu(II) ion into Cu(I) ion, which shows approximately 100-1000-fold enhancement in terms of antibacterial activity [7,33] reductive action of NH2OH. Besides, CuFe2O4/NH2OH reaction also mediated a significant change in O 1s electronic property.…”
Section: Reduction Of Surface Cu(ii) Into Cu(i) By Hydroxylaminementioning
confidence: 96%
See 3 more Smart Citations
“…It has been previously reported that NH 2 OH was able to efficiently transform Cu(II) ion into Cu(I) ion, which shows approximately 100-1000-fold enhancement in terms of antibacterial activity [7,33] reductive action of NH2OH. Besides, CuFe2O4/NH2OH reaction also mediated a significant change in O 1s electronic property.…”
Section: Reduction Of Surface Cu(ii) Into Cu(i) By Hydroxylaminementioning
confidence: 96%
“…The results showed that, at a concentration of 0.1, 0.2, 0.4, and 1 g/L CuFe 2 O 4 nanoparticles, the E. coli inactivation rate was 0.27-, 2.71-, 3.55-, and 4.74-log, respectively (Figure 5a), suggesting a dose-dependent CuFe 2 O 4 nanoparticle-induced reduction of bacterial viability. This is presumably because more exposed Cu(I) species mediated by NH 2 OH reduction acted as a highly potent antibacterial agent [32,33]. We subsequently evaluated the effect of NH 2 OH concentration.…”
Section: Enhanced Bactericidal Performance Of Copper Ferrite By Hydroxylamine Additionmentioning
confidence: 99%
See 2 more Smart Citations
“…The burdens of both the viral outbreaks and the bacterial infections could be mitigated via a single coating with the dual functionality of being antiviral and antibacterial. Different materials were used as a coating that combines antiviral and antibacterial functions, such as silver nanoparticles, TiO 2 , small-molecule organics, polymers, and Cu-containing surfaces ( Kim et al, 2015 ; Si et al, 2018 ; Gurunathan et al, 2020 ; Balasubramaniam et al, 2021 ). The antiviral and antimicrobial mechanism of these materials involves different pathways, such as reactive oxygen species (ROS) production, contact killing, and membrane depolarization by the dissolution of metal ions.…”
Section: Introductionmentioning
confidence: 99%